The Characteristics and Distribution of Congenital Heart Disease in Outpatient Clinic and Inpatient Ward of RSUD Dr. Soedono Madiun East Java in Year 2015 - Finariawan Finariawan; Syifa Mahmud S.A. (ACI (Acta Cardiologia Indonesiana), 2018)
Background: Congenital heart disease is a heart abnormality that presents at birth and fatal in the majority of the case. Congenital heart disease affecting up to 8-10 in every 1,000 newborn. Methods: This study was a descriptive research about the characteristics and distribution of congenital heart disease at ward and clinic of a government hospital in East Java for a year, by investigating medical record from 1 January 2015 – 31 December 2015. We classified and analyzed the patients based on the different groups of age, gender, type of congenital heart disease, the age of first diagnosed, nutritional status, co-morbidities of the disease, medical intervention, and the funding. Result: Total sample from this research was 49 subjects, consist of 53% male and 46% female. CHD was mostly diagnosed in the first year of life (75%), with acyanotic CHD as the most common type. Malnutrition was found in 51% of the subjects. Nonsurgical medical intervention was the most common management performed to treat the condition (97%). The funding with National Health Insurance (PBI or non-PBI) was used in more than half of the subjects (51%). Conclusion: As the conclusion, CHD was commonly found in the first year of life with noncyanotic type dominated the CHD patients. As the highly cost of this disease, it was surprising that only half of the subjects were covered by National Health Insurance. A good funding resource was really needed to make sure the treatment plan of the diseases was well executed.